Investigations on foliar epidermal characteristics in some Acanthaceae - D.A. Patil2, Patil, A.M.1* and (Current Botany, 2011)
The paper communicates observations on foliar epidermal characteristics of hitherto uninvestigated 22 species belonging 17 genera of the family Acanthaceae. Except few other types, diacytic type of stomata in generally noticed. The other types are rarely to occasionally on the same foliar surface. The other foliar features such as stomatal index and frequency, types of subsidiaries, stomatal abnormalities, cell inclusions, cell wall contours, etc. are described in detail. Their taxonomic significance is discussed pertinently.